Investigation of cationic ring-opening polymerization of 2-oxazolines in the “green” solvent dihydrolevoglucosenone - Borova, Solomiia; Luxenhofer, Robert (Beilstein Journal of Organic Chemistry, 2023)
For about the last ten years, poly(2-oxazoline)s have attracted significant attention as potential material for biomedical applications in, e.g., drug delivery systems, tissue engineering and more. Commonly, the synthesis of poly(2-oxazoline)s involves problematic organic solvents that are not ideal from a safety and sustainability point of view. In this study, we investigated the cationic ring-opening polymerization of 2-ethyl-2-oxazoline and 2-butyl-2-oxazoline using a variety of initiators in the recently commercialized "green" solvent dihydrolevoglucosenone (DLG). Detailed 1H NMR spectroscopic analysis was performed to understand the influence of the temperature and concentration on the polymerization process. Size exclusion chromatography and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry were performed to determine the molar mass of the resulting polymers. Our work shows clearly that the solvent is not inert under the conditions typically used for the cationic ring-opening polymerization, as evidenced by side products and limited control over the polymerization. However, we could establish that the use of the 2-ethyl-3-methyl-2-oxazolinium triflate salt as an initiator at 60 °C results in polymers with a relatively narrow molar mass distribution and a reasonable control over the polymerization process. Further work will be necessary to establish whether a living polymerization can be achieved by additional adjustments.
Keywords: 2-alkyl-2-oxazolines; matrix-assisted laser desorption/ionization mass spectrometry; nuclear magnetic resonance; polymerization kinetics